Evaluation of regional logistics performance for land freight along the developmental Syrian axis: Tartous – AlFarqulus - Aldahhak, Kamal; Darwish, Osama (European Spatial Research and Policy, 2025)
The study developed a spatial Decision Support System (DSS) to assess the impact of land freight logistics on regional development and create an evaluation map in a GIS environment. By designing a tri-level conceptual framework and applying the Fuzzy Analytic Hierarchy Process (FAHP), real stakeholders were involved at each evaluation level according to their roles. The system was integrated into GIS for final analysis and applied to the developmental Syrian axis of Tartous–Homs–Al-Farqulus using 2018 data. The results highlighted the importance of the relationships between evaluation criteria in identifying the role of freight logistics in regional planning and achieving broader developmental outcomes.